Respiratory Impairment after Early Red Cell Transfusion in Pediatric Patients with ALI/ARDS - Surender Rajasekaran; Dominic Sanfilippo; Allen Shoemaker; Scott Curtis; Sandra Zuiderveen; Akunne Ndika; Michael Stoiko; Nabil Hassan (Critical Care Research and Practice)
Introduction. In the first 48 hours of ventilating patients with acute lung injury (ALI)/acute respiratory distress syndrome (ARDS), a multipronged approach including packed red blood cell (PRBC) transfusion is undertaken to maintain oxygen delivery. Hypothesis. We hypothesized children with ALI/ARDS transfused within 48 hours of initiating mechanical ventilation would have worse outcome. The course of 34 transfused patients was retrospectively compared to 45 nontransfused control patients admitted to the PICU at Helen DeVos Children’s Hospital between January 1st 2008 and December 31st 2009. Results. Mean hemoglobin (Hb) prior to transfusion was 8.2 g/dl compared to 10.1 g/dl in control. P/F ratio decreased from 135.4±7.5 to 116.5±8.8 in transfused but increased from 148.0±8.0 to 190.4±17.8 (P<0.001) in control. OI increased in the transfused from 11.7±0.9 to 18.7±1.6 but not in control. Ventilator days in the transfused were 15.6±1.7 versus 9.5±0.6 days in control (P<0.001). There was a trend towards higher rates of MODS in transfused patients; 29.4% versus 17.7%, odds ratio 1.92, 95% CI; 0.6–5.6 Fisher exact P<0.282. Conclusion. This study suggests that early transfusions of patients with ALI/ARDS were associated with increased ventilatory needs.